"This world we live in was written by men, about men and for men": Attitudes and experiences of women in corporate boards in Akureyri for gender quotas - Sigursteinsdóttir, Hjördís; Helgadóttir, Kristín (School of Social Sciences, 2023)
The purpose of the study was to examine the proportion of women on corporate boards in Akureyri and their attitudes and experience with regard to the gender quota law. The data used was three-fold, statistical data, an online survey and semi-structured interviews. The research questions were: (1) What is the proportion of women on the boards of companies in Akureyri in the years 2011-2017? (2) Has the number of women on the boards of companies in Akureyri increased or decreased more in the years 2011-2017 compared to in general in Iceland? (3) What are the attitudes of board members with regard to gender quotas on boards and their experiences? The results show that the proportion of women on corporate boards in Akureyri was 14% in 2011 and rose to 36% in 2017. The increase was greater for companies in Akureyri than for the whole country. Attitudes towards the gender quota were generally positive and some considered it a necessary action to equalize the gender ratio on corporate boards and change prevailing attitudes within society, but participants still experienced little change even though the gender quota was bound by the law. It is important to impose penalties on companies that do not meet the requirements of at least 40% of women or men on company boards, because only this way can the human resources of society be utilized properly. Tilgangur rannsóknarinnar var að skoða hlutfall kvenna í stjórnum fyrirtækja á Akureyri og kanna viðhorf þeirra til kynjakvótalaganna og upplifun þeirra af þeim. Notaðar voru upplýsingar frá Creditinfo um kynjahlutfall í stjórnum fyrirtækja, tekin viðtöl við stjórnarfólk og framkvæmd spurningalistakönnun. Settar voru fram eftirfarandi rannsóknarspurningar: (1) Hvert er hlutfall kvenna í stjórnum fyrirtækja á Akureyri á árunum 2011–2017? (2) Hefur konum í stjórn fyrirtækja á Akureyri fjölgað eða fækkað meira á árunum 2011–2017 miðað við almennt á Íslandi? (3) Hver eru viðhorf stjórnarmanna fyrirtækja á Akureyri til kynjakvóta og hver er upplifun þeirra af honum? Niðurstöður ...